Analysis and Design of E-Commerce Applications on CV XYZ With User Centered Design Method - Jimi Asmara (The IJICS (International Journal of Informatics and Computer Science), 2021)
Along with the rapid and sophisticated development of technology, it has had a huge impact in today's life. This is demonstrated by the increasing development activities and development of information technology. One of the means used for the development of information technology is the use of computers. The purpose of this research is to analyze and design a website-based E-Commerce application so that it can help salesmen to get as many car purchase costumer databases as possible in order to be followed up in order to realize car purchases, attract many customers and maintain customer loyalty in order to further improve the sales process on the CV. XYZ. The method used for is with user centered design where in this method selurus activity involves the user. The result of this study is to produce a website-based application system design with the application of E-Commerce so as to make it easier for costumers to know the information of car loan simulations and monthly promos available at CV dealers. XYZ and also facilitated by being able to access independently through PCs, laptops and by using smartphones whenever and wherever consumers are, so as to increase sales on CV. XYZ